Method for testing binding power of lithium battery pole piece

Based on the principles of tape pasting and peeling, the residual thickness difference of the lithium battery electrode sheet after tape peeling is measured, which solves the problems of cumbersome and low efficiency of the existing testing methods, and achieves fast and accurate adhesion evaluation, which is suitable for efficient inspection of modern battery manufacturing lines.

CN119574426APending Publication Date: 2025-03-07LISHEN BATTERY (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671947.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing lithium battery electrode adhesive force testing methods are cumbersome, low efficiency, and high equipment costs, making it difficult to meet the efficient production needs of modern battery manufacturing lines.

Method used

Based on the principle of tape adhesion and peeling, the adhesive force is evaluated by measuring the remaining thickness difference of the lithium battery electrode sheet after tape peeling.

Benefits of technology

It simplifies the test process, significantly improves the testing efficiency, reduces equipment costs, and can quickly and accurately evaluate the adhesion of lithium battery poles, which is suitable for large-scale inspection on the production line.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119574426A_ABST
    Figure CN119574426A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium battery pole piece cohesive force testing method which comprises the following steps: S1, measuring the pole piece thickness of a preset detection area of a pole piece, and defining the pole piece thickness as a first pole piece thickness; s2, adhering a first adhesive tape section of the adhesive tape to the surface of the preset detection area; s3, the left end and the right end of the pole piece are wound around an unwinding end transmission roller and a winding end transmission roller correspondingly; s4, the opposite ends of the first adhesive tape section and the second adhesive tape section of the adhesive tape are fixedly connected with the first clamp and the second clamp correspondingly, and the adhesive tape is wound around the guide roller; s5, stripping a first adhesive tape section of the adhesive tape in a direction perpendicular to the upper surface of the lithium battery pole piece; s6, measuring the thickness of the pole piece in the preset detection area again, defining the thickness as the thickness of the second pole piece, and obtaining the difference between the thickness of the second pole piece and the thickness of the first pole piece; and S7, evaluating the pole piece adhesion strength according to the thickness difference value. According to the invention, the testing process can be simplified and the equipment cost can be obviously reduced while the testing precision of the bonding force of the battery pole piece is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for testing the bonding force of lithium battery pole pieces. Background Art

[0002] In sodium-ion and lithium-ion batteries, the positive and negative electrode materials undergo ion insertion and extraction during the charge and discharge process, which causes the volume of the battery active materials to expand. Due to this volume change, the active materials may fall off from each other or from the active materials to the current collector, thus affecting the performance and life of the battery.

[0003] In order to deal with this problem, a certain amount of binder is usually added during the battery manufacturing process. Binder plays a vital role in sodium-ion and lithium-ion batteries. It can tightly bond the active materials, conductive agents and current collectors together to ensure the stability of the battery pole structure during the charging and discharging process. The presence of binder has a significant impact on the cycle life and safety of the battery.

[0004] The bonding strength of battery electrodes is mainly affected by factors such as the amount of adhesive, the choice of foil and the manufacturing process, among which the amount of adhesive is the most important influencing factor.

[0005] However, the binder itself does not have conductive properties, so if too much is used, it will reduce the overall capacity of the battery, increase polarization during the charge and discharge process, and increase the manufacturing cost of the battery. On the contrary, if the amount of binder is too little, it may lead to insufficient bonding of the pole piece, resulting in incomplete pole pieces before the battery reaches its designed life. Therefore, it is particularly important to accurately control the amount of binder used and test and calibrate the bonding strength of the pole piece.

[0006] At present, a common method for testing the adhesion of battery pole pieces is to use peel strength as the main test indicator. Another common method is to soak the pole piece in a specific solution, then perform ultrasonic treatment, and finally remove moisture by baking. The adhesion is evaluated by weighing the powder dropped from the pole piece.

[0007] However, the existing testing methods are relatively cumbersome and inefficient. Although they can provide accurate data, they are often accompanied by complex operating procedures, high equipment costs, and long testing cycles. This is undoubtedly a major challenge for modern battery manufacturing lines that pursue efficient production.

[0008] Therefore, there is an urgent need to develop a new method that can not only ensure the test accuracy of battery electrode adhesion but also significantly improve the test efficiency. Summary of the invention

[0009] The purpose of the present invention is to provide a method for testing the bonding strength of lithium battery pole pieces in view of the technical defects in the prior art.

[0010] To this end, the present invention provides a method for testing the bonding strength of a lithium battery electrode, which comprises the following steps:

[0011] Step S1, selecting a preset detection area on the upper surface of the lithium battery electrode to be detected, and measuring the thickness of the lithium battery electrode in the preset detection area, and defining it as the first electrode thickness;

[0012] Step S2, tightly adhering the first tape segment A of the tape to the surface of the preset detection area of ​​the lithium battery electrode and leaving it for a preset time;

[0013] The adhesive tape comprises a first adhesive tape segment A and a second adhesive tape segment B connected together;

[0014] Step S3, passing the left and right ends of the lithium battery electrode around the unwinding end transmission roller and the winding end transmission roller respectively;

[0015] The transmission rollers at the unwinding end and the winding end are rotationally symmetrically distributed;

[0016] The first tape segment A of the tape is located on the upper surface of one end of the lithium battery pole piece adjacent to the unwinding end drive roller;

[0017] Step S4, fixing the ends of the first tape segment A and the second tape segment B of the tape opposite to each other to the first clamp M1 and the second clamp M2 respectively, and passing the tape around the guide roller;

[0018] The first tape segment A and the second tape segment B of the tape are arranged perpendicular to each other;

[0019] Step S5, peeling off the first tape segment A of the tape in a direction perpendicular to the upper surface of the lithium battery electrode at a constant speed;

[0020] Step S6, for the lithium battery electrode sheet from which the first tape segment A of the tape has been peeled off, measuring the thickness of the lithium battery electrode sheet in the preset detection area again and defining it as the second electrode sheet thickness, and then obtaining the thickness difference between the first electrode sheet thickness and the second electrode sheet thickness in step S1;

[0021] Step S7, evaluating the strength of the bonding force of the lithium battery electrode according to the thickness difference.

[0022] It can be seen from the technical solution provided by the present invention that, compared with the prior art, the present invention provides a method for testing the adhesion of lithium battery pole pieces, which is scientifically designed and is an innovative method for testing the adhesion of lithium ion battery pole pieces. The present invention is based on the principle of tape sticking and peeling, and directly tests the thickness of the remaining pole piece after the tape is peeled off. This technical means not only simplifies the test process of the adhesion of battery pole pieces while ensuring the accuracy of the test of the adhesion of battery pole pieces, but also significantly reduces the required equipment cost, which has great practical significance.

[0023] By applying the present invention, researchers and engineers can quickly and accurately evaluate the bonding strength of battery pole pieces, which is of great significance for battery performance optimization and quality control.

[0024] In addition, the simplicity of the test method used in the present invention means that it can be quickly implemented on a production line, thereby improving production efficiency and reducing battery failures caused by insufficient adhesion.

[0025] In addition, due to the low-cost nature of the present invention, even laboratories or small businesses with limited resources can adopt this technology, further promoting the popularization and innovation of lithium-ion battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A flow chart of a method for testing the bonding force of a lithium battery electrode provided by the present invention;

[0027] Figure 2 A schematic diagram of the working state of a method for testing the bonding force of a lithium battery electrode provided by the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0030] In the description of this patent, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", and "set" should be understood in a broad sense, for example, it can be fixedly connected or set, or it can be detachably connected or set, or connected or set in one piece. For ordinary technicians in this field, the specific meanings of the above terms in this patent can be understood according to specific circumstances.

[0031] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0032] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation modes.

[0033] See also Figure 1 , Figure 2 The present invention provides a method for testing the adhesion of lithium battery pole pieces, which is a rapid detection method for the adhesion of lithium ion battery pole pieces based on a tape stripping method. The present invention can quickly evaluate the adhesion by performing simple tape sticking and stripping operations combined with accurate measurement of the remaining pole piece thickness, thereby significantly improving detection efficiency and effectively reducing detection costs.

[0034] The testing method of the present invention comprises the following steps:

[0035] Step S1, selecting a preset detection area on the upper surface of the lithium battery electrode 4 to be detected, and measuring the thickness of the lithium battery electrode in the preset detection area, and defining it as the first electrode thickness;

[0036] In step S1, in specific implementation, the surface of the lithium battery electrode to be tested is flat and free of any contaminants to ensure the accuracy of the test results;

[0037] In step S1, in specific implementation, the preset detection area is a representative detection area;

[0038] It should be noted that a representative detection area is a flat electrode area without powder loss or foil leakage, and the electrode thickness and the electrode active material coating per unit area in this area are qualified (that is, the electrode thickness meets the pre-required qualified thickness, and the electrode active material coating per unit area meets the pre-requirements). The preset detection area in step S1 and the preset detection area in step S6 are the same area.

[0039] In step S1, in specific implementation, a high-precision thickness measuring instrument, a micrometer, is used to measure the thickness of the electrode in a preset detection area.

[0040] Step S2, tightly adhering the first tape segment A of the tape to the surface of the preset detection area of ​​the lithium battery electrode 4, and leaving it for a preset time;

[0041] The adhesive tape comprises a first adhesive tape segment A and a second adhesive tape segment B connected together;

[0042] It should be noted that the first tape segment A is used to bond the lithium battery pole piece, and the second tape segment B is not used to bond the lithium battery pole piece.

[0043] In step S2, in specific implementation, the width of the tape may be equal to the width of the lithium battery electrode sheet, or slightly smaller than or slightly larger than the width of the lithium battery electrode sheet;

[0044] In step S2, in specific implementation, the first tape section of the tape is closely attached to the lithium battery electrode sheet in the preset detection area to ensure that the tape is in full contact with the surface of the lithium battery electrode sheet, thereby ensuring the reliability of the detection;

[0045] In step S2, in specific implementation, a time length is preset, preferably 1 minute.

[0046] It should be noted that after the tape comes into contact with the lithium battery electrode, wait for a period of time (eg, 1 minute) to allow the adhesion between the tape and the electrode to reach a stable state, thereby ensuring the stability of the test results.

[0047] Step S3, passing the left and right ends of the lithium battery electrode 4 around the unwinding end transmission roller 2 and the winding end transmission roller 1 respectively;

[0048] The unwinding end drive roller 2 and the winding end drive roller 1 are rotationally symmetrically distributed;

[0049] The first tape segment A of the tape is located on the upper surface of one end of the lithium battery pole piece 4 adjacent to the unwinding end drive roller 2;

[0050] In step S3, in specific implementation, the unwinding end drive roller 2 and the winding end drive roller 1 are distributed longitudinally and are arranged parallel to each other.

[0051] Step S4, fixing the ends of the first tape segment A and the second tape segment B of the tape opposite to each other to the first clamp M1 and the second clamp M2 respectively, and passing the tape around the guide roller 3;

[0052] The first tape segment A and the second tape segment B of the tape are arranged perpendicular to each other;

[0053] In step S4, in specific implementation, the first tape segment A of the tape is horizontally distributed, and the second tape segment B of the tape is vertically distributed;

[0054] In step S4, in specific implementation, the guide rail 3 is located between the first clamp M1 and the second clamp M2;

[0055] The first tape section A of the tape is located between the guide roller 3 and the unwinding end drive roller 2;

[0056] In step S4, in specific implementation, the bottom surface of the guide roller 3 is in tangential contact with the top surface of the first tape segment A of the tape;

[0057] The right side surface of the guide roller 3 is in tangential contact with the left side surface of the second tape segment B of the tape;

[0058] It should be noted that, for the present invention, the first clamp M1 and the second clamp M2 can be any type of clamp that can fix the tape. Only two clamps are needed as long as they do not hinder the operation, rotation, etc. of other mechanisms of the patented device.

[0059] Step S5, peeling off the first tape segment A of the tape in a direction perpendicular to the upper surface of the lithium battery electrode 4 at a constant speed (e.g., 100 mm / min);

[0060] In step S5, in specific implementation, the unwinding end drive roller 2 is controlled to rotate clockwise, and the winding end drive roller 1 is controlled to rotate counterclockwise, so as to realize the first tape segment A of the tape being peeled off in a direction perpendicular to the upper surface of the lithium battery electrode 4;

[0061] It should be noted that the unwinding end drive roller 2 and the winding end drive roller 1 rotate in opposite directions;

[0062] In step S5, in a specific implementation, during the process of peeling off the first tape segment A of the tape, it is observed whether the electrode material falls off during the peeling process to evaluate the strength of the adhesive force.

[0063] It should be noted that, in the present invention, the guide roller 3 is used to cooperate with the first clamp M1 and the second clamp M2 as well as the unwinding end drive roller 2 and the winding end drive roller 1 to ensure the vertical peeling of the first tape segment A of the tape;

[0064] The first clamp M1 is used to fix one end of the tape (the end having the first tape segment A), and the second clamp M2 is used to fix the other end of the tape (the end having the second tape segment B);

[0065] In step S5, in specific implementation, the winding end drive roller 1 is connected to the power output shaft of the servo motor M3;

[0066] The servo motor M3 is used to drive the winding end transmission roller 1 to rotate counterclockwise at a constant speed.

[0067] It should be noted that the winding end drive roller 1 is equipped with a servo motor M3 to achieve constant speed peeling of the tape. The first tape segment A of the tape is used to adhere to the upper surface of the lithium battery electrode, and segment B is the remaining tape portion connected to the first tape segment A.

[0068] It should be noted that the winding end drive roller 1 is linked to the driving device (servo motor M3) (for example, connected to the output shaft of the motor through a coupling), and rotates accordingly under the drive of the driving device. Of course, there is also a corresponding support frame to support the various components of the entire device. The above-mentioned driving device, support frame, etc. are common existing structures and will not be described in detail here.

[0069] Step S6, for the lithium battery electrode sheet from which the first tape segment A of the tape has been peeled off, measuring the thickness of the lithium battery electrode sheet in the preset detection area again and defining it as the second electrode sheet thickness, and then obtaining the thickness difference between the first electrode sheet thickness and the second electrode sheet thickness in step S1;

[0070] In step S6, in specific implementation, a high-precision thickness measuring instrument, a micrometer, is used to measure the thickness of the electrode sheet in the detection area after peeling, and the thickness is compared with the thickness of the electrode sheet before peeling, and the thickness difference is recorded to quantify the magnitude of the bonding force;

[0071] Step S7, evaluating the strength of the bonding force of the lithium battery electrode according to the thickness difference;

[0072] In step S7, in a specific implementation, the bonding strength of the lithium battery pole piece is evaluated according to the size of the thickness difference; the smaller the thickness difference, the stronger the bonding strength of the lithium battery pole piece, and vice versa, the weaker the bonding strength of the lithium battery pole piece.

[0073] After step S7, the method further includes the following steps:

[0074] Step S8, compare the thickness difference with a preset thickness difference qualified standard value. When it is less than or equal to the thickness difference qualified standard value, it is judged that the bonding force of the battery electrode is qualified and meets the requirements. Otherwise, it is unqualified and does not meet the requirements.

[0075] It should be noted that, for the present invention, the qualified standard for adhesion (i.e., the qualified thickness difference standard) can be set according to actual needs, and the test results can be compared with the standard to determine whether the electrode meets the requirements, thereby ensuring the performance and safety of the battery.

[0076] In summary, the present invention provides a simple, rapid and low-cost method for detecting the adhesion of lithium-ion battery pole pieces, which helps to improve the quality control efficiency in the battery production process.

[0077] Compared with the prior art, the present invention has the following beneficial technical effects:

[0078] 1. The present invention can intuitively reflect the degree of influence of the tape on the surface of the pole piece during the peeling process by measuring the difference between the remaining pole piece thickness and the original pole piece thickness. In this way, the bonding force of the pole piece can be directly inferred, thereby evaluating its bonding performance.

[0079] 2. The advantages of the method of the present invention are: easy to operate, low cost, and can provide test results quickly and accurately. This is undoubtedly a huge advantage for large-scale and rapid detection needs on the production line. Traditional adhesion testing methods often require complex equipment and high costs, and the testing process is cumbersome and time-consuming. In contrast, the method of the present invention greatly simplifies the test process, improves test efficiency, and makes real-time detection on the production line possible.

[0080] 3. The method of the present invention has high flexibility and applicability, and can be widely applied to various types of pole piece materials. Whether it is a metal pole piece, a ceramic pole piece or a composite pole piece, the bonding force can be evaluated by this method. This makes the present invention have broad application prospects in the fields of battery manufacturing, electronic packaging, etc.

[0081] 4. The present invention is an efficient and low-cost testing method for evaluating the bonding force of the electrode by cleverly combining the tape sticking and peeling processes. This method can not only meet the large-scale and rapid detection needs on the production line, but also has high flexibility and applicability, and has broad application prospects.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for testing the bonding strength of a lithium battery electrode, characterized in that: The following steps are involved: Step S1, selecting a preset detection area on the upper surface of the lithium battery electrode (4) to be detected, and measuring the thickness of the lithium battery electrode in the preset detection area, and defining it as the first electrode thickness; Step S2, tightly adhering the first tape segment A of the tape to the surface of the preset detection area of ​​the lithium battery electrode (4), and leaving it to stand for a preset time; The adhesive tape comprises a first adhesive tape segment A and a second adhesive tape segment B connected together; Step S3, passing the left and right ends of the lithium battery electrode (4) around the unwinding end transmission roller (2) and the winding end transmission roller (1) respectively; The unwinding end drive roller (2) and the winding end drive roller (1) are rotationally symmetrically distributed; The first tape section A of the tape is located on the upper surface of one end of the lithium battery pole piece (4) adjacent to the unwinding end drive roller (2); Step S4, fixing the ends of the first tape segment A and the second tape segment B of the tape opposite to each other to the first clamp M1 and the second clamp M2 respectively, and passing the tape around the guide roller (3); The first tape segment A and the second tape segment B of the tape are arranged perpendicular to each other; Step S5, peeling off the first tape segment A of the tape in a direction perpendicular to the upper surface of the lithium battery electrode (4) at a constant speed; Step S6, for the lithium battery electrode sheet from which the first tape segment A of the tape has been peeled off, measuring the thickness of the lithium battery electrode sheet in the preset detection area again and defining it as the second electrode sheet thickness, and then obtaining the thickness difference between the first electrode sheet thickness and the second electrode sheet thickness in step S1; Step S7, evaluating the strength of the bonding force of the lithium battery electrode according to the thickness difference.

2. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S1, the surface of the lithium battery electrode to be inspected is flat and free of any contaminants.

3. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S3, the unwinding end drive roller (2) and the winding end drive roller (1) are longitudinally distributed and arranged parallel to each other.

4. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S4, the first tape section A of the tape is horizontally distributed, and the second tape section B of the tape is vertically distributed.

5. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S4, the guide rail (3) is located between the first clamp M1 and the second clamp M2; The first adhesive tape section A of the adhesive tape is located between the guide roller (3) and the unwinding end transmission roller (2).

6. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S4, the bottom surface of the guide roller (3) is in tangential contact with the top surface of the first tape segment A of the tape; The right side surface of the guide roller (3) is in tangential contact with the left side surface of the second adhesive tape section B of the adhesive tape.

7. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S5, the unwinding end drive roller (2) is controlled to rotate clockwise, and the winding end drive roller (1) is controlled to rotate counterclockwise, so as to peel off the first tape segment A of the tape in a direction perpendicular to the upper surface of the lithium battery electrode (4).

8. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S5, the winding end drive roller (1) is connected to the power output shaft of the servo motor M3; The servo motor M3 is used to drive the winding end transmission roller 1 to rotate counterclockwise at a constant speed.

9. The method for testing the bonding strength of a lithium battery pole piece according to claim 1, characterized in that: In step S7, the smaller the thickness difference is, the stronger the bonding force of the lithium battery pole piece is, and vice versa, the weaker the bonding force of the lithium battery pole piece is.

10. The method for testing the bonding strength of a lithium battery pole piece according to any one of claims 1 to 9, characterized in that: After step S7, the method further includes the following steps: Step S8, compare the thickness difference with a preset thickness difference qualified standard value. When it is less than or equal to the thickness difference qualified standard value, it is judged that the bonding force of the battery electrode is qualified and meets the requirements. Otherwise, it is unqualified and does not meet the requirements.